PENGARUH PEMBERDAYAAN KELUARGA TERHADAP PENGENDALIAN OBESITAS - Bertalina, Bertalina; Mulyani, Roza (Politeknik Kesehatan Tanjung Karang, 2020)
World's population 2,2 billion obesity. Besides, overweight and obesity have a risk of developing diabetes (44%), ischemic heart disease (23%), and cancer (7-41%). The main risk factors that cause obesity are behavioral factors, which are unhealthy eating patterns, plus insufficient consumption of fiber (fruit and vegetables), lack of physical activity, and smoking. The study aimed to determine the effect of family empowerment on obesity control in Hajimena Public Health Center, South Lampung. The research variable was family empowerment with a balanced nutrition diet, routine physical activity measured before, and after being educated. The study was conducted in July-November 2018. The type of research was a Quasi experiment, the results of sample calculations obtained a sample of 66 people. The results showed there were differences in fat, vegetable, sugar, salt and sweet foods intake before and after intervention with a value of p 0.048, 0,022, 0,001, 0,008 and 0,025. There was no difference in intake, energy, protein, carbohydrate, fruit, before and after the intervention with p-values of 0,576, 0,229, 0,583, and 0,930. There are differences in physical activity before and after the intervention with a p-value of 0,001. The Health Center can collaborate with the school in overcoming obesity programs by conducting counseling in schools and evaluating nutritional status.